Effects of Nitrogen Rates on Nitrogen Accumulation, Ascorbic Acid and Essential Oil Contents in Parsley - Ceylan, Safak; Yoldas, Funda; Cakici, Hakan; Mordogan, Nilgun; Bayram, Emine (Asian Journal of Chemistry, 2010)
The effects of increased N rates (0, 100, 200 and 300 kg N ha-1) on total-N, NO3-N, NO2-N accumulation, ascorbic acid, essential oil contents in parsley leaf and stalk during the seven harvesting times at two sowing times were investigated. Nitrogen rates had a significant effect on nitrogen, ascorbic acid and essential oil accumulation in leaf and stalk during the harvesting times in both sowing times. The highest values except essential oil were observed with 300 kg N ha-1 treatment Nitrate content in leaf did not exceed the acceptable norm in parsley. Just only the 300 kg N ha-1 treatment in stalk was high when it was compared with literature. In addition, these criteria were changed during the harvesting time and still, only NO3-N, NO2-N, ascorbic acid, essential oil contents in leaf were affected by sowing times significantly.